New framework of assessing the impacts of companies on regional sustainable development: The Sakha case - Gutman, S. (2022)
his paper is based on the proposed hypothesis: the activities of a company (especially a large, backbone company) in the social, environmental and economic spheres have a corresponding impact on certain aspects of the sustainable development of the region. The goal of the study is to prove this relationship at a conceptual level using indicators of sustainable development applied at different levels of socio-economic systems. The paper addresses a relevant gap in the literature: the absence of frameworks allowing the assessment of the interactions and intendancies between levels. To do this, the literature on this issue was studied and it was proved that there were no studies with a similar framework. The study draws on the systems of sustainable development indicators, suggested in literature and used for the assessment of sustainable development at the regional and company's level and proposes a framework to integrate them. For that it uses the classical balance scorecard (BSC) tools - the strategic maps both for a region and a company. The Republic of Sakha (Yakutia) in Russian Federation and public joint stock company “ALROSA” were chosen as the basic object of research at the regional and corporate level, respectively. The built strategic maps reflect the decomposition of the main strategic goal and contain an interdependent set of sustainable development indicators for each level, which can be used to assess and monitor the results of the relevant strategies. Then, a new conceptual framework reflecting the impact of the l company's activities on the sustainable development of the region is proposed. The framework includes the performance indicators of the company and the region by three dimensions of sustainable development - environmental, social, and economic. On the basis of the conceptual scheme of the relationship, it is possible in the future to build econometric models based on the proposed indicators. The identified quantitative assessments in this case will make it possible to make strategic management decisions that will maximize the positive effect of the implementation of the sustainable development strategy in the region using the potential of companies.